Mindful eating questionnaired: eating control, emotional eating and conscious nutrition trio - Köse, Gizem; Çıplak, Ertuğrul (MATTIOLI 1885, 2020)
Objective: Present study, it was aimed to determine the relationship between university students' mindful eating according to their age, body mass index and gender, and also to find mindful eating and subscales correlations and relationships, especially between emotional eating. Methods: This cross-sectional study was conducted 400 randomly selected undergraduate students in a university in Turkey. Participants completed Mindful Eating (MEQ) questionnaire that included questions related to their eating discipline, mindfulness, eating control, disinhibition, etc. Results: In our study, participants were aged between 18-26 and 35.0% were female and 65.0% were male, the mean BMI (kg/m(2)) was 22.93 +/- 2.93. There were no significant difference between participants applied with national examination and taken the talent selection in any statistical assessment (p>0.05). Mean MEQ score was 3.14 +/- 0.44 and there was no statistically significant difference between males (3.14 +/- 0.45) and females (3.14 +/- 0.43) (p>0.05). Obese group was found to be having less MEQ scores than any other BMI classes and participants in normal weight group had the highest MEQ score (p<0.05). Obese participant found to have less disinhibition, eating discipline, emotional eating, and conscious nutrition scores (p<0.05). In correlations, when age increased, BMI (r=0.122, p=0.015), mean MEQ score (r=0.156, p=0.002), emotional eating (r=0.250, p=0.000), eating discipline (p=0.124, p=0.013), and interference (r=0.128, p=0.010) increased statistically significantly. There was strong correlation between total MEQ and subscales (p<0.01). Eating control, emotional eating, mindfulness, conscious nutrition and interference had a strong correlation (p<0.01). Conclusion: Young adulthood is an important stage of life to create lifelong eating and nutritional habits. With age, body mass index increases as expected, but this can lead to impair life quality. It is vital to detect mindful eating status and make an intervention about nutrition and eating.
Keywords: Mindful Eating; Mindfulness; Nutrition; Emotional Eating; Body Mass İndex